2004
DOI: 10.1111/j.1523-1755.2004.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Homozygosity for uromodulin disorders: FJHN and MCKD-type 2

Abstract: The study shows that individuals with two UMOD mutations are viable, but they do have more severe disease on average than heterozygotes. This family sheds light on the possible disease mechanism in this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 25 publications
2
22
0
1
Order By: Relevance
“…Occurrence of homozygosity for a dominant UMOD mutation with more pronounced clinical symptoms was reported (27). Mutations can cause loss-ofphysiological function or gain-of-toxic function of the protein.…”
Section: Discussionmentioning
confidence: 97%
“…Occurrence of homozygosity for a dominant UMOD mutation with more pronounced clinical symptoms was reported (27). Mutations can cause loss-ofphysiological function or gain-of-toxic function of the protein.…”
Section: Discussionmentioning
confidence: 97%
“…Since FJHN/MCKD2 represents an autosomal dominant disorder and most subjects are heterozygous with the homozygous patient being a rarity, 19) heterozygous Tg mice were used in this study. However, further investigation is needed using homozygous Tg mice because homozygous patients exhibit an earlier onset of hyperuricemia and renal insufficiency than heterozygous patients for the same mutation.…”
Section: Discussionmentioning
confidence: 99%
“…This prediction turned out to be exactly the case. Rezende-Lima et al (50) showed in a family with familial juvenile hyperuricemic nephropathy and medullary cystic kidney disease type II that homozygous carriers of C255Y had a much earlier onset of hyperuricemia and faster progression to end stage renal disease than the heterozygous carriers of the same mutation. By demonstrating a trapping effect of a mutated THP toward its wild-type counterpart, we are by no means excluding the global effects of the cytotoxicity of the mutant on the protein synthesis and trafficking in the host cells.…”
Section: Discussionmentioning
confidence: 99%